(ENT 300) Business Model Canvas SS Cookies / Siti Salwa Husain - Husain, Siti Salwa (2020)
My business product is a cookie. I named my business product is SS COOKIES. Since I is someone who love to eat cookies, I decided to bring out my own cookies with the taste that I actually want and I believe all people out there also have a good taste same goes to me if they are really a cookies lovers they will know which are the best cookies. I will feel regret if I am not produced my own cookies since I also know how and learn about business and entrepreneurship. Cookies are a baked or cooked food that is typically small, flat and sweet. It usually contains flour, sugar and some type of oil or fat. It may include other ingredients such as raisins, oats, chocolate chips, nuts, etc. This is according to our taste because cookies can put in varieties ingredient that we can eat better and satisfied. SS COOKIES is special because the taste is promising you satisfaction while eating and the best it has varieties of choice such raisin, oats, dates, varieties of dry fruits, almonds, chocolate chip and any kind of nuts. Cookies or biscuits may be mass-produced in factories, made in small bakeries or homemade. Cookies are often served with beverages such as milk, coffee or tea and sometimes "dunked", an approach which releases more flavour from confections by dissolving the sugars, while also softening their texture. Cookies are most commonly baked until crisp or just long enough that they remain soft, but some kinds of cookies are not baked at all. The softness of the cookie may depend on how long it is baked. A general theory of cookies may be formulated this way. Despite its descent from cakes and other sweetened breads, the cookie in almost all its forms has abandoned water as a medium for cohesion. Water in cakes serves to make the base (in the case of cakes called "batter") as thin as possible, which allows the bubbles, responsible for a cake's fluffiness to better form. In the cookie, the agent of cohesion has become some form of oil. Thus a cake made with butter or eggs instead of water is far denser after removal from the oven.